PENGARUH KOMPENSASI, KEPEMIMPINAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (Survei Pegawai Rumah Sakit Islam Amal Sehat Sragen) - Siti Almunawaroch, Alwi Suddin & Lamidi (Universitas Slamet Riyadi, 2017)
The purpose of research is to analyze the significance of the effect ofcompensation, leadership, competence and discipline to employee performance as wellas the dominant variable influence on employee performance. The usefulness of thisresearch for the Islamic Charity Hospital Healthy Sragen is can be used asconsideration for policy making in improving employee performance through theprovision of compensation, leadership, competence and work discipline. This study usessurvey method, the type of data used quantitative and qualitative data, the data sourceused primary data and secondary data. The population in this study were all employeesat the Islamic Charity Hospital Healthy Sragen as many as 315 people. The number ofsamples in this study as many as 83 people, the number of samples used as many as 79people, the sampling technique using proportional cluster random sampling. Datacollection methods are used: questionnaires and documentation. Data analysistechnique used to test the validity, reliability test, classic assumption test and multiplelinear regression analysis. In conclusion: Compensation, leadership, competence anddiscipline significant partially effect on employee performance. The dominant variableinfluence on employee performance is variable work discipline.Keywords: compensation, leadership, competence, discipline of work and employeeperformance